The impact of green Marketing strategies of fast fashion brands on purchasing behavior of select college level students in Metro Manila - Abanilla, Gian Keith L. (Animo Repository, 2022)
The rise in environmental deterioration and consumer awareness of such issues has resulted in a widespread adoption of green marketing methods by businesses. Green marketing is the practice of creating and selling products and/or services that are environmentally friendly. Green marketing has progressed from a fad to a way of life. Environmental degradation is currently one of the world's most concerning issues, owing to a variety of factors including industrialization, technological advancements, urbanization, and human intervention, which has resulted in climate change, water and air pollution, land degradation, and other issues. According to Chauhan, Choudhary, and Kushwah (2015), the best solution to address the aforementioned environmental concern is to include green concepts into all current development initiatives. The primary goal of the study is to determine if fast fashion firms' green marketing methods have an impact on the purchasing behavior of select college students in Metro Manila when it comes to green garments. A quantitative explanatory research design was used to determine the impact of green marketing strategies, such as green advertising, green branding, green labeling, and green packaging, on the purchasing behavior of select college level students in Metro Manila. The data were gathered through an online survey that was conducted among a group of Metro Manila college students. The following analyses were carried out: descriptive, correlation, linear regression, and moderation. The proponents deduced from the outcomes of this study that Green Marketing Strategy does have a substantial impact on the Green Purchasing Behavior of college level students in Metro Manila.